Enhanced scheduling traffic light model using discrete event simulation for improved signal timing analysis - Zainal Abidin, Zaheera; Abal Abas, Zuraida; Lim, Ee Theng; Abdul Rahman, Ahmad Fadzli Nizam; Shibghatullah, Abdul Samad (Asian Research Publishing Network (ARPN), 2015)
Most traffic light today used pre-timed traffic light, traffic light using sensors and traffic light which displaying a countdown timer. However, the existing methods consume a long time of vehicle queuing and waiting the traffic light signals to change, which created congestion at intersection of roads. In this paper, the proposed model enhanced the scheduling traffic light, which simulates the vehicle behaviour based on discrete event simulation and queue theory. Therefore, the simulation becomes more realistic and contributes to accurate outcome. This work focuses on the analysis of the average waiting time for the vehicle in three cases: heavy, medium and low traffic volume. The most optimum traffic signal timing is the one with minimum waiting time for the vehicles. Moreover, the new model solves the critical traffic congestion problem not only in simulation but also in real environment, which drivers take the longest average waiting time is 86 seconds while the shortest average waiting time is 64 seconds at the junction although in heavy traffic congestion. An extensive simulations have been conducted in this work in which a green interval as a control parameter is selected.